Paradoxical immunodeficiencies—When failures of innate immunity cause immunopathology. Issue 9 (24th May 2022) - Kolter, Julia; Henneke, Philipp; Groß, Olaf; Kierdorf, Katrin; Prinz, Marco; Graf, Laura; Schwemmle, Martin
Abstract: Innate immunity facilitates immediate defense against invading pathogens throughout all organs and tissues but also mediates tissue homeostasis and repair, thereby playing a key role in health and development. Recognition of pathogens is mediated by germline‐encoded PRRs. Depending on the specific PRRs triggered, ligand binding leads to phagocytosis and pathogen killing and the controlled release of immune‐modulatory factors such as IFNs, cytokines, or chemokines. PRR‐mediated and other innate immune responses do not only prevent uncontrolled replication of intruding pathogens but also contribute to the tailoring of an effective adaptive immune response. Therefore, hereditary or acquired immunodeficiencies impairing innate responses may paradoxically cause severe immunopathology in patients. This can occur in the context of, but also independently of an increased microbial burden. It can include pathogen‐dependent organ damage, autoinflammatory syndromes, and neurodevelopmental or neurodegenerative diseases. Here, we discuss the current state of research of several different such immune paradoxes. Understanding the underlying mechanisms causing immunopathology as a consequence of failures of innate immunity may help to prevent life‐threatening disease. Abstract : Typically, immunopathology is associated with unwanted gain‐of‐function of immune responses. Here, we discuss the current state of research how deficiencies of innate immunity can paradoxically cause immunopathology as well